2021
DOI: 10.1038/s41467-021-22173-5
|View full text |Cite
|
Sign up to set email alerts
|

The folate cycle enzyme MTHFD2 induces cancer immune evasion through PD-L1 up-regulation

Abstract: Metabolic enzymes and metabolites display non-metabolic functions in immune cell signalling that modulate immune attack ability. However, whether and how a tumour’s metabolic remodelling contributes to its immune resistance remain to be clarified. Here we perform a functional screen of metabolic genes that rescue tumour cells from effector T cell cytotoxicity, and identify the embryo- and tumour-specific folate cycle enzyme methylenetetrahydrofolate dehydrogenase 2 (MTHFD2). Mechanistically, MTHFD2 promotes ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(73 citation statements)
references
References 40 publications
3
63
0
Order By: Relevance
“…Proprotein convertase subtilisin/keying type 9 (PCSK9) has been documented to block intratumoural infiltration by T cells. 5 , 6 In the present study, we found that cholesterogenic cases expressed significantly higher levels of MTHFD2 and PCSK9 than other cases (Figure 2G ). Furthermore, as shown in Figure 2H , 10 pathways were significantly enriched in the cholesterogenic group (false discovery rate (FDR) < 0.05).…”
Section: Figuresupporting
confidence: 63%
“…Proprotein convertase subtilisin/keying type 9 (PCSK9) has been documented to block intratumoural infiltration by T cells. 5 , 6 In the present study, we found that cholesterogenic cases expressed significantly higher levels of MTHFD2 and PCSK9 than other cases (Figure 2G ). Furthermore, as shown in Figure 2H , 10 pathways were significantly enriched in the cholesterogenic group (false discovery rate (FDR) < 0.05).…”
Section: Figuresupporting
confidence: 63%
“…Among them, COX-2 is inductively expressed and is almost undetectable We also found that the NF-κB pathway can increase the expression of c-Myc to increase the expression of PD-L1. 22 Programmed death-ligand 1 (PD-L1, B7-H1) is a member of the B7 family of cell surface ligands. 23 It is a membrane ligand that is found significant upregulating on the surface of many cells in inflammatory and/or carcinogenic lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor-in ltrating immune cells in the TME can independently be adopt to predict sentinel lymph node status and patient survival, and the above ndings support a prognostic role of MTHFD2 in pan-cancer [4,24]. Therefore, we used TIMER to explore the association between immune in ltration levels and MTHFD2 expression level in various cancer types.…”
Section: Relationship Between Mthfd2 Expression and In Ltrating Immune Cells In Ovarian Cancermentioning
confidence: 96%